The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1021/acs.chemrev.6b00801
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of Protein Methyltransferases and Demethylases

Abstract: Post-translational modifications of histones by protein methyltransferases (PMTs) and histone demethylases (KDMs) play an important role in the regulation of gene expression and transcription and are implicated in cancer and many other diseases. Many of these enzymes also target various nonhistone proteins impacting numerous crucial biological pathways. Given their key biological functions and implications in human diseases, there has been a growing interest in assessing these enzymes as potential therapeutic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
252
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 235 publications
(261 citation statements)
references
References 689 publications
(1,479 reference statements)
4
252
0
Order By: Relevance
“…16 Dysregulation of GLP and G9a has been associated with numerous human diseases, including cancer, inflammatory diseases, and neurodegenerative disorder. 1724 …”
Section: Introductionmentioning
confidence: 99%
“…16 Dysregulation of GLP and G9a has been associated with numerous human diseases, including cancer, inflammatory diseases, and neurodegenerative disorder. 1724 …”
Section: Introductionmentioning
confidence: 99%
“…For example, PKMT inhibitors, such as BIX-01294, UNC0638, UNC0642 (G9a/GLP), EPZ005687, GSK126, EI1, UNC1999, EPZ-6438, CPI-1205 (EZH2/EZH1), EPZ004777, SGC0946, EPZ-5676 (DOT1L), AZ-505 and LLY507 (SMYD2) are valuable chemical tools for further understanding biological functions of the targeted enzymes and have already been widely used in evaluating the therapeutic potential of these proteins (Table 1). [9,10] In addition, highly potent, selective, substrate-competitive PRMT inhibitors including MS023 (type I PRMTs), TP-064 (CARM1), EPZ015666 (PRMT5) and EPZ020411 (PRMT6) have been accomplished, suggesting that the substrate-binding grooves of PRMTs can also be successfully targeted (Table 1). [9,12,13] The discovery of the first allosteric PRMT3 inhibitor and the development of the PRMT3 chemical probe SGC707 have demonstrated that the allosteric binding site of PRMT3 can be exploited to yield potent, selective, and cell-active inhibitors, opening the door for discovering allosteric inhibitors of other PRMTs (Table 1).…”
Section: Recent Progress In Discovery Of Inhibitors Of Pmtsmentioning
confidence: 99%
“…[9,10] In addition, highly potent, selective, substrate-competitive PRMT inhibitors including MS023 (type I PRMTs), TP-064 (CARM1), EPZ015666 (PRMT5) and EPZ020411 (PRMT6) have been accomplished, suggesting that the substrate-binding grooves of PRMTs can also be successfully targeted (Table 1). [9,12,13] The discovery of the first allosteric PRMT3 inhibitor and the development of the PRMT3 chemical probe SGC707 have demonstrated that the allosteric binding site of PRMT3 can be exploited to yield potent, selective, and cell-active inhibitors, opening the door for discovering allosteric inhibitors of other PRMTs (Table 1). [14] Moreover, the discovery of the covalent SETD8 inhibitor MS453 has demonstrated that cysteine residues in active sites of PMTs can be selectively targeted (Table 1).…”
Section: Recent Progress In Discovery Of Inhibitors Of Pmtsmentioning
confidence: 99%
See 2 more Smart Citations